Kenakalan remaja yang semakin merajalela di era globalisasi - Sugiarti, Dwi (Maliki Interdisciplinary Journal, 2024)
Technology is currently developing very rapidly. The discussion focuses on society and the younger generation, especially adolescent development, understanding bad behavior in adolescents, development, understanding bad behavior in adolescents, understanding social media, factors that can cause adolescents to become infected. This has a significant impact on efforts to prevent teenagers from becoming infected. Some of the material presented is relevant to the younger generation. Teenage harassment is an abnormal behavior carried out by the younger generation. Social media is an online platform where people can follow, share and create content such as blogs, social networks, Wikipedia, forums and virtual worlds. Apart from social media, factors that predict the occurrence of hypokalism in the first step to improving yourself and your family teenagers include family factors, environmental and social factors, internal factors, constructs, information technology, and so on. Factors that cause youth violence must be accompanied by youth prevention efforts. Preventing malnutrition among adolescents requires an understanding of the challenges most adolescents face. This shows that the prevalence of malnutrition among the younger generation is usually unavoidable. Therefore, should start with positive business encouragement from the people around you. This can develop and solve various problems that occur during adolescence.